Semaglutide, liraglutide and tirzepatide: Comparison of effectiveness in the treatment of obesity – a literature review - Baran, Karolina; Jankowska, Marlena; Jańczyk, Natalia; Mędrysa, Karolina; Pokrzepa, Jakub; Presak, Michał; Blecharz, Gabriela; Szwech, Julia; Winkowska, Alicja; Machalica, Jan (Quality in Sport, 2024)
Introduction Obesity is a complex, multifactorial condition characterized by an excessive accumulation of body fat. It is widely recognized as a major public health issue due to its strong association with numerous chronic diseases. [1][2] The use of GLP-1 receptor agonists in obesity treatment began with the recognition that these drugs, initially developed for type 2 diabetes, could significantly reduce body weight due to their effects on appetite regulation and satiety. Liraglutide was the first to be approved specifically for obesity, followed by semaglutide, The development of tirzepatide, which targets both GLP-1 and GIP receptors, has further expanded the potential for obesity treatment. As clinical evidence continues to support their efficacy and safety, GLP-1 receptor agonists are becoming an important tool in the management of obesity, offering a promising option for individuals struggling with weight and related health conditions [3][4][5]. Aim of the study The aim of this study was to compare the effectiveness of semaglutide, liraglutide and tirzepatide in reducing body weight in obesity. Materials and methods The article was created based on the PubMed and Cochrane databases. The literature was analyzed using the fallow keywords: Obesity treatment, liraglutide, tirzepatide, semaglutide, glucagon-like peptide-1 (GLP-1) receptor agonists Results The research proved that tirzepatide is more effective in reducing body weight compared to semaglutide and liraglutide [6][7]. Conclusion Thanks to the comparison of results from multiple studies, we can assume that, at this point, tirzepatide is the most effective pharmacological treatment for obesity, which, when used in combination with lifestyle changes, provides a lasting effect on weight reduction and, consequently, helps treat obesity-related comorbidities[6][8].